Biodegradable scaffolds facilitate epiretinal transplantation of hiPSC-Derived retinal neurons in nonhuman primates. (15th October 2021) - Luo, Ziming; Xian, Bikun; Li, Kang; Li, Kaijing; Yang, Runcai; Chen, Mengfei; Xu, Chaochao; Tang, Mingjun; Rong, Huifeng; Hu, Dongpeng; Ye, Meifang; Yang, Sijing; et al.
Abstract: Transplantation of stem cell-derived retinal neurons is a promising regenerative therapy for optic neuropathy. However, significant anatomic differences compromise its efficacy in large animal models. The present study describes the procedure and outcomes of human-induced pluripotent stem cell (hiPSC)-derived retinal sheet transplantation in primate models using biodegradable materials. Stem cell-derived retinal organoids were seeded on polylactic-coglycolic acid (PLGA) scaffolds and directed toward a retinal ganglion cell (RGC) fate. The seeded tissues showed active proliferation, typical neuronal morphology, and electrical excitability. The cellular scaffolds were then epiretinally transplanted onto the inner surface of rhesus monkey retinas. With sufficient graft–host contact provided by the scaffold, the transplanted tissues survived for up to 1 year without tumorigenesis. Histological examinations indicated survival, further maturation, and migration. Moreover, green fluorescent protein-labeled axonal projections toward the host optic nerve were observed. Cryopreserved organoids were also able to survive and migrate after transplantation. Our results suggest the potential efficacy of RGC replacement therapy in the repair of optic neuropathy for the restoration of visual function. Statement of significance: In the present study, we generated a human retinal sheet by seeding hiPSC-retinal organoid-derived RGCs on a biodegradable PLGA scaffold. We transplanted this retinal sheet onto the inner surface of the rhesus monkey retina. With scaffold support, donor cells survive, migrate and project their axons into the host optic nerve. Furthermore, an effective cryopreservation strategy for retinal organoids was developed, and the thawed organoids were also observed to survive and show cell migration after transplantation. Graphical abstract: Image, graphical abstract